Lean accounting and its rolls for calculated costs on value stream (Journal of Accounting and Financial Studies ( JAFS ), 2013)
At the last two decades , The environment has witnessed tremendous changes in many fields with the huge competition , various technological development and customer satisfaction , that are reflected in economic units a doption for lean production system .                       Lean Accounting that has appeared as aresponse for changes occurred of economic units adoption for lean accounting system instead of wide production system : through it management of economic units has been changed from management by top departments into management by value flows : has provide new method for accounting costs according to value flow instead of products